Remittance Behavior of the Filipino Immigrants in Iceland - Priscela Ycot Sigurðsson 1971- (2015)
The presence of Filipino immigrants in Iceland is the result of the “pull“ factor more than the “push“ factor. It is evident that more Filipino women who are married to an Icelandic citizen are coming to Iceland. Seeing more opportunities for work, better living conditions, safety and equality among individuals are the determinants that make Filipino immigrants more likely to stay and live in Iceland along with their existing family, relatives and friends, especially if they are employed and earn a decent income to support themselves and their family back home in the Philippines. The researcher conducted a survey using a qualitative and quantitative sampling methods with a focus group of individuals in order to understand the remittance behavior of the Filipino immigrants in Iceland. Results show that among the 51 participants, there are more females than males, who are active remitters. The majority of the participants are employed individuals whose earnings are partly sent regularly to their families in the Philippines. In spite of the financial crisis which hit Iceland in 2008 that impact the flow of foreign currency transfer, affecting many Filipino immigrants, the finding suggests that none of the participants stopped sending financial support to their families and loved ones in the Philippines. Limited options for money transfer services in Iceland result in higher charges to some extent, but the satisfaction levels are positive among the participants, particularly those who use the available fast services of the money in minutes by MoneyGram and Western Union. The participants trust the convenience these services offer and the easy access for the recipient to claim transferred funds at the other end.